RESPON KETAHANAN DAN KANDUNGAN SENYAWA FENOL ENAM VARIETAS KEDELAI (Glycine max (L.) Merrill) TERHADAP PENYAKIT BUSUK PANGKAL BATANG (Sclerotium rolfsii Sacc.) - Fitria Dwi Damayanti; Rachmi Masnilah (Jember University Press, 2020)
decreased, one of which is caused by stem rot disease. This disease is caused by Sclerotium rolfsii which is an important pathogen in soybean plants. Planting using resistant varieties is an effective, inexpensive, and easily adopted method for farmers. In addition, it can minimize the use of pesticides. This study aims to study the resistance of six soybean varieties to S. rolfsii attacks that cause stem rot disease. The study was conducted at the Situbondo Green House and at the Disease Laboratory of the Faculty of Agriculture, University of Jember in April-November 2019. Soybeans were used as many as 6 varieties, namely Anjasmoro, Devon 1, Dering 1, Grobogan, Dega 1, and Dena 1. The research was carried out using a complete random design sampling (CRD) consisting of 6 treatments and 4 replications. Observational variables studied were incubation period, disease severity, disease incidence, and phenol compound content. Data from the test results were analyzed using variance, if the data obtained were significantly different at the 5% test level, then the analysis was continued using the DMRT-test (Duncan's multiple range test) at the 5% level. The results showed that the use of different varieties influenced the variables of incubation period, disease severity, disease incidence, and phenol content. The fastest incubation period for Anjasmoro (V1) variety is on the 5th day, while the longest incubation period is on Dena 1 (V6) variety on the 8th day. The highest disease severity was found in the Anjasmoro (V1) variety (78.33%) with the category very susceptible to stem rot disease. The lowest disease severity is in Dena 1 (V6) variety (30%) with resistance to stem rot disease. The highest disease incidence was in Anjasmoro (V1) (100%) variety, and the lowest was in Dena 1 (V6) variety (30%). Each soybean plant variety tested had different phenol compounds. An increase in phenol compounds after the plants were inoculated with S.rolfsii. The Dena 1 (V6) variety has the highest phenol compound content compared to the other five varieties. Keywords: Stem Rot, Sclerotium rolfsii, Soybean Varieties